Elevated Levels Of Serum Uric Acid In Pre-Eclamptic Women - DR. B. VODELU; DR. S. LAXMI NARAYANA (International Journal of Pharma and Bio Sciences, 2015)
The purpose of the present study is to estimate serum uric acid levels in preeclamptic, eclamptic and normotensive groups to identify women who are at high risk of developing the disease early in pregnancy. The study may provide possible biochemical parameter in toxemias of pregnancy. This is because early identification of biochemical markers of the disease would not only facilitate to identify those at increased risk for pre-eclampsia but also help in determining those patients likely to benefit from interventional measures. This study was conducted in the Department of Biochemistry, Gandhi Medical College, Secunderabad, Telangana, State, India. The cases for the study were selected from the antenatal outpatient, Gandhi Hospital, Secunderabad. A total of 34 subjects were selected and categorized into three groups. 22 among 34 women, were Pregnancy Induced Hypertensive (B.P. >140/90 mmHg), who were considered as the experimental group and remaining 12 were normotensive (B.P. <140/90 mmHg) taken as controls (n êžŠ12). The experimental group was further categorized into two groups, having 16 women in preeclampsia (n êžŠ 16), and six in eclampsia (n êžŠ 6). The data obtained was subjected to statistical tests of mean and standard deviation utilizing the SPSS-7.5 version. One-way analysis of variance (ANOVA) was utilized to compare the mean serum uric acid levels among pregnant women. The serum uric acid levels studied in various study groups showed a significant increase in pre-eclamptic (n êžŠ 16) and eclamptic (n êžŠ 6) the difference being statistically significant at p ≤ 0.001. The mean serum uric acid level values for women with pre-eclampsia (5.80 ± 0.59 mg/dl, n êžŠ 16) and eclampsia (6.37 ± 0.25 mg/dl, n êžŠ 6) were significantly higher than those of controls (4.56 ± 0.36 mg/dl, n êžŠ 12) which is statistically significant at p < 0.001. Moreover, it was also experimentally found that the individual values of observed SUA in preeclamptics and eclamptics were relatively higher than those of the average values of normotensives. Although mean serum uric acid values are elevated in women with preeclampsia, the clinical utility of serum uric acid values in differentiating various hypertensive diseases of pregnancy appears to be limited. In the setting of chronic hypertension, however, a serum uric acid level of > or = 5.5 mg/dl could identify women with an increased likelihood of having superimposed preeclampsia.